Riparian forest of the humid tropics of Mexico: A study case and critical aspects for their successful restoration - Meli, Paula; Ruiz, Lucía; Aguilar, Rocío; Rabasa, Alejandra; Rey Benayas, José María; Carabias, Julia (Instituto de Ecología, A.C., 2017)
Riparian ecosystems harbor significant biodiversity and support essential ecological functions that affect ecosystem services provision for human well-being. Anthropogenic disturbances often exceed the natural resilience of these ecosystems thus resulting in their degradation. Ecological restoration promotes restoring biodiversity and riparian ecosystems services, but its success depends on several aspects. This work bases on a study case to exemplify the problem of restoration from an ‘integral’ perspective and discusses ecological, socio-economic and legal aspects that can influence the success of the restoration of these forests. While ecological aspects have been considerably developed, information on economic (e.g. production costs), social (e.g. social acceptance) and legal constraints (e.g. incorporation of restoration in public programs) are still limited for restoration being applied at broader scales. Estimating ecosystem services that could be restored from the restoration of riparian forests may help to integrate these aspects. Addressing these aspects at the local level will provide information for the future development of more efficient regional strategies in terms of the ecological benefit-socioeconomic cost ratio. Finally, we discuss some recommendations relating to the conservation, management and restoration of riparian ecosystems in the humid tropics of Mexico.